ASSOCIATION BETWEEN ENERGY AND MACRONUTRIENTS INTAKE WITH ANTHROPOMETRIC INDICATORS IN CHILDREN - Yuliana, Yuliana; Sidiartha, I Gusti Lanang (Medicina, 2014)
Antropometric indicator is the most widely used measurement of children’s nutritional status. The three main indicators that use to deûne undernutrition are underweight, stunting, and wasting, willrepresent different histories of nutritional insult to children. Adequate nutrition is a prerequisite to good health and one important determinant of growth and development. The objective of this study wasto investigate possible association between energy and macronutrients intake with anthropometric indicators. A cross-sectional study held at Jempiring Pediatric Wards Sanglah Hospital Denpasarfrom October until December 2013. Chi square and logistic regression test were used for detecting associations between energy and macronutrients intake with anthropometric indicators. A P-valueless than 0.05 was considered statistical significant. A total of 152 children were analyzed. Underweight was associated with inadequate intake of total energy, carbohydrate, and protein with PR 5.47 (95% CI 1.20 to 24.96), 4.29 (95% CI 1.03 to 117.86), 3.40 (95% CI 1.04 to 11.13), respectively. Stunting was associated with inadequate intake of total energy and protein with PR 4.76 (95% CI 1.56 to 14.57) and 13.41 (95% CI 4.42 to 40.68), respectively. Wasting was associated only with inadequate intake of total energy with PR 4.14 (95% CI 1.74 to 9.83). It can be concluded that underweight, stunting, and wasting showed association with inadequate energy and macronutrients intake. [MEDICINA 2014;45:3-8]